Análise das consequências e agravamento da covid-19 nas pessoas obesas em um município trinacional - Pona, Leonardo Bueno (2023)
Introduction: Given the health crisis scenario imposed by the emergence of the new coronavirus 2019 (COVID-19), the issue of obesity has gained space for discussion in public health because it is considered a high-risk factor for mortality in patients affected by the disease. Objective: To verify the possible consequences and the worsening of the infection by COVID-19 in obese patients treated in a Brazilian city in the international triple border area. Methodology: This was an ecological, retrospective and descriptive study, with secondary data provided by the Municipal Health Department of Foz do Iguaçu, covering positive notifications for COVID-19 between March 2020 and December 2021. We included records of patients with laboratory confirmation, without exclusion by sex, age, or race. We employed the simple descriptive and inferential statistical technique for quantitative data analysis, performed in the Statistical Package for Social Sciences software, free license. A value of less than 5% was set for a significant relationship between the variables observed (p<0.05). The presentation of the data was by means of comparative tables, with absolute and relative frequencies. Results: From the total of 3,274 notification forms, it was observed male predominance (59%), average age of 57±18 years brown skin color (58%), and no vaccination record (88.5%). An obesity rate of 15.5% was found, with heart disease (p<0.003), immunodepression (p<0.001), liver disease (p<0.008), and kidney disease (p<0.015) as the main risk factors. The main findings of this study relate to the low rate of obesity, hospitalization and mortality among patients diagnosed with COVID-19 in Foz do Iguaçu. Conclusion: Obesity was associated with increased hospitalizations and need for mechanical ventilation support in obese patients with worse clinical prognosis.